COVID-19 as a Research Dynamic Transformer: Emerging Cross-Disciplinary and National Characteristics - Ohniwa, Ryosuke L.; Kijima, Joji; Fukushige, Mizuho; Ohneda, Osamu (Frontiers in Big Data, 2021)
The outbreak of the COVID-19 pandemic has had an unprecedented impact on humanity as well as research activities in life sciences and medicine. Between January and August 2020, the number of coronavirus-related scientific article was roughly 50 times more than the number of articles published in the entire year of 2019 in PubMed. It is necessary to better understand the dynamics of research on COVID-19, an emerging topic, and suggest ways to understand and improve the quality of research. We analyze the dynamics of coronavirus research before and after the outbreaks of SARS, MERS, and COVID-19 by examining all the published articles from the past 25 years in PubMed. We delineate research networks on coronaviruses as we identify experts’ background in terms of topics of previous research, affiliations, and international co-authorships. Two distinct dynamics of coronavirus research were found: i) In the cases of regional pandemics, SARS and MERS, the scope of cross-disciplinary research remained between neighboring research areas; ii) In the case of the global pandemic, COVID-19, research activities have spread beyond neighboring disciplines with little transnational collaboration. Thus, COVID-19 has transformed the structure of research on coronaviruses as an emerging issue. Knowledge on COVID-19 is distributed across the widest range of disciplines transforming research networks well beyond the field of medicine but within national boundaries. Given the unprecedented scale of COVID-19 and the nationalization of responses, the most likely way forward is to accumulate local knowledge with the awareness of transdisciplinary research dynamics.